2020
DOI: 10.1177/2633366x20917988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of production temperature on thermal and mechanical properties of polystyrene–fly ash composites

Abstract: This study was conducted to produce a novel construction material by using two different types of waste material consisting of fly ash and fragmented polypropylene (PP). These two materials were mixed on various ratios, and samples with smooth surface were obtained by compressing with 50 kg of weight after each mixture is heated on temperatures of 225 C, 250 C, and 275 C and poured into the molds. Thermal and mechanical tests were performed on the prepared samples. As a result, with the evaluation of two waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Definitely the least favourable effect of modification was achieved for the 15% FA concrete. Although this substitute was characterized by fine granulation and high reactivity (Figures 8, 9) with a larger amount of this additive, the effect of reducing the strength of the composite, which was characteristic for FA, during the period below 90 days of curing became visible [95,118]. Moreover, it was observed that the results When analysing the results obtained for both f cm and f ctm , it should be stated that the highest indices of strength, both compressive and tensile, had concrete with a quaternary binder, containing a smaller proportion of FA, i.e., 5%.…”
Section: Mechanical Parametersmentioning
confidence: 99%
“…Definitely the least favourable effect of modification was achieved for the 15% FA concrete. Although this substitute was characterized by fine granulation and high reactivity (Figures 8, 9) with a larger amount of this additive, the effect of reducing the strength of the composite, which was characteristic for FA, during the period below 90 days of curing became visible [95,118]. Moreover, it was observed that the results When analysing the results obtained for both f cm and f ctm , it should be stated that the highest indices of strength, both compressive and tensile, had concrete with a quaternary binder, containing a smaller proportion of FA, i.e., 5%.…”
Section: Mechanical Parametersmentioning
confidence: 99%
“…Researchers have searched for alternatives to glass fibers from both natural (e.g., wood flour, rice husks) (La Mantia and Morreale, 2006;Tong et al, 2014;Chen et al, 2018) and man-made sources (e.g., fly ash from coal production). Previous studies have explored the integration of fly ash into various polymers such as polypropylene (PP), polyethylene terephthalate (PET), polystyrene (PS), and high density polyethylene (HDPE) (Rebeiz et al, 1995;Satapathy and Kothapalli, 2015;Yao et al, 2019;Bicer, 2020;Ajorloo et al, 2021). Many of the results have demonstrated promise.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the results have demonstrated promise. For example, fly ash was determined to disperse well throughout a polymer matrix, leading to uniform mechanical properties (Bicer, 2020;Ajorloo et al, 2021). Additionally, one study reported that when blended with PET, ash filler could improve tensile strength without causing changes to the glass transition temperature or thermal degradation (Rebeiz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the principles of sustainable construction, attempts should be made to minimize the use of ordinary Portland cement (OPC) for the production of concrete by replacing it with other materials. Such actions, which are undoubtedly pro-ecological, directly affect: reduction of greenhouse gas emissions (GHG) to the atmosphere, such as CO 2 , NO, NO 2 [ 1 , 2 , 3 ]; reduction of heat and electricity consumption [ 4 , 5 , 6 ]; reduction of the extraction of natural resources [ 7 , 8 , 9 ]; possibility to utilize industrial wastes, such as fly ash (FA) or silica fume (SF) [ 10 , 11 , 12 ]. …”
Section: Introductionmentioning
confidence: 99%